Health Assets in a Global Context Theory, Methods, Action - Morgan, Antony.; Morgan, Antony.; Ziglio, Erio.; Ziglio, Erio.; Davies, Maggie.; Davies, Maggie. (Springer New York : Imprint: Springer, 2010)
Health Assets in a Global Context: Theory, Methods, Action Edited by Antony Morgan, Maggie Davies, and Erio Ziglio As global health inequities continue to widen, policymakers are redoubling their efforts to address them. Yet the effectiveness and quality of these programs vary considerably, sometimes resulting in the reverse of expected outcomes. While local political issues or cultural conflicts may play a part in these situations, an important new book points to a universal factor: the prevailing deficit model of assessing health needs, which puts disadvantaged communities on the defensive while ignoring their potential strengths. The asset model proposed in Health Assets in a Global Context offers a necessary complement to the problem-focused framework by assessing multiple levels of health-promoting aspects in populations, and promoting joint solutions between communities and outside agencies. The book provides not only rationales and methodologies (e.g., measuring resilience and similar elusive qualities) but also concrete examples of asset-based initiatives in use across the world on the individual and community levels, including: • Strengthening the assets of disadvantaged women (Germany). • Sustainable community-based development programs (India). • Using parental assets to control child malaria (West Africa). • Asset/evidence-based health promotion in the schools (Romania). • Evaluating asset-based programs (Latin America). • Using social capital to promote health equity (Australia). Health Assets in a Global Context offers a new, positive lens for viewing the world’s most resistant public health crises, making it fundamental reading for researchers and graduate students in public health, especially those involved in health promotion, health disparities, social determinants of health, and global health.